Pengaruh Kelengkapan Produk, Kualitas Pelayanan, dan E-WoM Terhadap Loyalitas Pelanggan di Toko Tabacstore Mataram - Ekadana, I Gede (Postgraduate, University of Mataram, 2026)
Customer loyalty plays a major role in the business world because customer loyalty can express behaviors related to products or services for companies as part of customer mentality. The purpose of this study is to determine the influence of product completeness, service quality, and E-Wom on customer loyalty at Tabacstore. The type of research used in this study is quantitative research. The location of this study was conducted at Tabacstore Mataram, West Nusa Tenggara. The respondents required for this study amounted to 65, which was rounded up to 75 respondents to reduce errors. The types of instruments used to find facts in this study are: Questionnaire, Interview, and Documentation. The research procedure uses instrument tests, namely validity test and reliability test, Classical assumption tests using data normality test, Heteroscedasticity, Multicollinearity, multiple linear regression analysis, correlation analysis. Furthermore, the model uses F-test (Model Feasibility), Coefficient of determination (R²), and T-test. Based on the research results, it can be concluded that the product completeness variable (X1) affects buyer loyalty (Y). Service quality (X2) affects buyer loyalty (Y), and (Electronic Word of Mouth) E-WoM affects customer loyalty (Y) at Tabacstore Mataram